The Role of Coverage Coordinator in the Production of Insert Infotainment Program at Trans TV - Ergia Maharani Putri; Muhammad Muttaqien (Jogjakarta Communication Conference (JCC), 2026)
Insert (short for Informasi Selebriti, stylized as!nsert) is an entertainment news program broadcast on Trans TV, which holds a high-quality index in the information category according to the Komisi Penyiaran Indonesia (KPI). This research aims to analyze and describe the role of the Coverage Coordinator by utilizing the POAC management functions (Planning, Organizing, Actuating, and Controlling) and Gatekeeping theory. Employing a descriptive qualitative approach, data were collected through interview techniques with the Producer, Coverage Coordinator, and Reporters, further supported by documentation. The data were then processed through the stages of data reduction, data presentation, and conclusion drawing. The results of this research indicate that the Insert Coverage Coordinator executes content briefing and production management in accordance with POAC principles and applies Gatekeeping theory throughout the process, thereby successfully increasing the program's quality index and audience appeal.